Self-Care in Palliative Healthcare Professionals: A Qualitative Study - Andrea Bovero; Maria Federica Spada; Alessandra Loreta Cito; Alexa Victoria Pidinchedda; Chiara Tosi; Sara Carletto (Nursing Reports)
Background/Objectives: Self-care strategies enhance well-being and facilitate coping with emotional distress, particularly for palliative care professionals dealing with end-of-life issues. This study aimed to explore self-care practices among healthcare professionals working in palliative care settings by analyzing their perceptions and reflections. Methods: A total of 36 palliative care professionals participated in one of four focus group discussions on the topic of self-care. The discussions were transcribed and analyzed using qualitative content analysis. Results: Participants identified several self-care strategies as the most effective and the most frequently used, including lifestyle and emotional coping techniques. The meaning of self-care and its functions were delineated. Participants also identified factors that either facilitate or hinder self-care and discussed its impact on team well-being. Not all participants had received professional self-care training, and some struggled to identify their own strategies. However, participation in the focus group discussions was perceived as beneficial for improving work dynamics, group cohesion, communication, and freedom of expression. Conclusions: The positive feedback from the focus groups suggests that they are a valuable tool for fostering further discussions on self-care. The study recommends increasing the implementation of self-care strategies and professional training to enhance the well-being of palliative care professionals, their teams, and the patients they care for.